1986
DOI: 10.1136/bmj.293.6558.1329
|View full text |Cite
|
Sign up to set email alerts
|

Increased concentration of circulating calcitonin gene related peptide during normal human pregnancy.

Abstract: Statistical analyses-Analysis of variance and two tailed Student's t test were used after log transformation to make the data distribution normal. IntroductionPregnancy is accompanied by profound changes in maternal haemodynamics. Plasma volume expands considerably, but changes in the peripheral vascular tone usually prevent an increase in blood pressure. The precise regulation of such changes has not been documented.Calcitonin gene related peptide is a potent vasoactive peptidel-' that normally circulates in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(59 citation statements)
references
References 16 publications
3
55
0
1
Order By: Relevance
“…It has been reported that both estrogen and progesterone, which are ovarian hormones, stimulate CGRP peptide synthesis in dorsal root ganglia neurons through increasing CGRP mRNA (Gangula et al 2000a). Plasma CGRP levels in rats and humans have been reported to increase with pregnancy and decrease postpartum (Stevenson et al 1986, Saggese et al 1990, Gangula et al 2000b. These findings suggest that ovarian hormones may be responsible for increased CGRP levels in the circulation.…”
Section: Discussionmentioning
confidence: 53%
“…It has been reported that both estrogen and progesterone, which are ovarian hormones, stimulate CGRP peptide synthesis in dorsal root ganglia neurons through increasing CGRP mRNA (Gangula et al 2000a). Plasma CGRP levels in rats and humans have been reported to increase with pregnancy and decrease postpartum (Stevenson et al 1986, Saggese et al 1990, Gangula et al 2000b. These findings suggest that ovarian hormones may be responsible for increased CGRP levels in the circulation.…”
Section: Discussionmentioning
confidence: 53%
“…PlGF may play a role especially after the first trimester, when serum concentration begins to rise as the placenta grows and matures (115). Another candidate is calcitonin gene-related peptide (CGRP), which increases in the blood during early pregnancy in women (183). CGRP is a potent vasodilator (187), and therefore, it may contribute to systemic and renal vasodilation of pregnancy.…”
Section: Molecular Mechanisms Of Renal Vasodilation In Pregnancymentioning
confidence: 99%
“…Furthermore, CGRP-containing nerve fibers are present in the human uterus (7), and CGRP relaxes contractile activity in the human uterus and fallopian tubes (7). CGRP is also present in the circulation, and the plasma levels of this neuropeptide are increased during human pregnancy (5,20), indicating that CGRP may play a role in the regulation of human myometrial contractility during pregnancy and labor. We examined the in vitro relaxant effects of CGRP on human myometrium using concentrations of CGRP from 10 -11 to 10 -6 M, based upon the physiologic concentration of circulatory CGRP in humans (10 -10 M; refs.…”
Section: Discussionmentioning
confidence: 99%